Does it Take More Than Ideals? How Counter-Ideal Value Congruence Shapes Employees’ Trust in the Organization - Schuh, Sebastian C. (Journal of business ethics, 2018)
Research on value congruence rests on the assumption that values denote desirable behaviors and ideals that employees and organizations strive to approach. In the present study, we develop and test the argument that a more complete understanding of value congruence can be achieved by considering a second type of congruence based on employees’ and organizations’ counter-ideal values (i.e., what both seek to avoid). We examined this proposition in a time-lagged study of 672 employees from various occupational and organizational backgrounds. We used difference scores as well as polynomial regression and response surface analyses to test our hypotheses. Consistent with our hypotheses, results reveal that counter-ideal value congruence has unique relations to employees’ trust in the organization that go beyond the effects of ideal value congruence. We discuss theoretical and practical implications of this expanded perspective on value congruence.